Augmenting surveys with social media discourse on the workings of democracy from a cross-national perspective - Reveilhac, Maud; Morselli, Davide (Frontiers in Political Science, 2024)
This paper introduces an unsupervised framework that illustrates how insights gathered from opinion surveys regarding the functionality of democracy can be connected to social media messages of politicians on an international scale. By concentrating on the influence of social media messages from elected officials, the study adopts a “top-down” theoretical approach that links citizens’ attitudes towards democracy with the viewpoints about democracy expressed by politicians within social media discourses. Using a word embedding classification strategy, democracy-related themes are extracted from politicians’ messages. The research is conducted across 11 European countries, namely, Austria, Finland, France, Germany, Greece, Italy, the Netherlands, Spain, Sweden, and the United Kingdom. Switzerland is also included in the study because of its direct democracy system. The 10th round of the European Social Survey serves as the basis for assessing citizens’ democratic attitudes. The study encompasses two main analytical segments. First, aggregated analyses conducted at the country level reveal the degree of alignment between prominent democracy-related themes present in politicians’ discourse and citizens’ perceived significance of these same themes. Second, individual-level connections between social media data and survey respondents are established through their preferred political party (or orientation). Variable importance analysis is subsequently applied to explore which democracy-related themes conveyed by politicians hold significance in predicting public contentment with democracy.